2021
DOI: 10.1039/d0ay02086a
|View full text |Cite
|
Sign up to set email alerts
|

Developing a systematic method for extraction of microplastics in soils

Abstract: Microplastic extraction efficency from soil depends on soil compostion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(52 citation statements)
references
References 55 publications
3
38
1
2
Order By: Relevance
“…Recovery rates in compost samples show a matching trend to OECD arti cial soil with increasing recovery rates in increasing density but they were lower in every solution in compost compared to OECD arti cial soil. The decreased recovery rates can be attributed to the content of organic matter which was also shown in other studies (Radford et al 2021). Compost had a content of organic matter triple the amount of arti cial soil.…”
Section: Recovery Rates Of Mpssupporting
confidence: 82%
See 2 more Smart Citations
“…Recovery rates in compost samples show a matching trend to OECD arti cial soil with increasing recovery rates in increasing density but they were lower in every solution in compost compared to OECD arti cial soil. The decreased recovery rates can be attributed to the content of organic matter which was also shown in other studies (Radford et al 2021). Compost had a content of organic matter triple the amount of arti cial soil.…”
Section: Recovery Rates Of Mpssupporting
confidence: 82%
“…IR-spectra of conventional polymers with H 2 O 2 at 60°C also showed "no major deviations from control"(Hurley et al 2018). Effects of H 2 O 2 on MPs were also not detected by(Radford et al 2021). The results of spectral changes t results of size change for MB with H 2 O 2 at 60°C as impact factor.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…As a measure of quality assurance, recovery rates (positive control) must be determined and reported. Numerous authors have pointed out the importance and necessity of spike-and-recovery approach as a part of standardized protocol for extraction of microplastic particles [2 , 11 , 18 , 25] . Still, the challenge remains since recovery success may differ due to protocol applied, variability of environmental matrices and polymer properties such as type, shape and size [3 , 25] .…”
Section: Methods Detailsmentioning
confidence: 99%
“…This finding is comparable across other media. For example, Radford et al (2021) 70 found PET had the lowest recovery rates in soil, whereas LDPE had the highest recovery rates. In some cases, the high-density polymers can be recovered with the higher-density solutions, such as zinc bromide (ZnBr 2 ).…”
Section: Discussionmentioning
confidence: 99%